Role of civil society in health care: Mechanisms for realizing universal health coverage in vulnerable communities of India - Jayaraman, Anuja; Fernandez, Armida (Frontiers in Public Health, 2023)
The role of civil society as a partner in the delivery of primary health care is well established. The pandemic placed a great burden on the existing public health system and civil society stepped forward not only to help the vulnerable population to mitigate challenges that subsequently arose but also to fill the gaps the pandemic exposed in India's health care system. The objective of this paper is to provide mechanisms for realizing universal health coverage by strengthening primary health care from the perspective of civil society. The paper uses examples of efforts of SNEHA, a non-profit organization working on the health of women and children in informal settlements of Mumbai and other civil society organizations working with vulnerable or hard-to-reach populations. We use existing literature, field data, reports and published work over the years. We find that civil society helps the health system to connect with difficult-to-reach populations and achieve wider coverage. They can also build the capacity of frontline staff in the public systems in formal and informal ways. They can recommend ways to change the attitudes and motivations of these workers. Civil society organizations with their close connection with the community can play the part of a ‘gap-filler’ and data messenger. Finally, they can refer people to appropriate health facilities minimizing out-of-pocket expenditure on health.